Język prawniczy wobec zmian w prawie: [Legal language in the face of law changes] (Studia Prawnicze / The Legal Studies, 1991)
Na podstawie sporu wokół norm planowania gospodarczego Autor przedstawia konsekwencje, jakie spowodowało w języku prawniczym pojawienie się zmian w prawie związanych z tymi normami. Przykładając wagę do metodologicznych konsekwencji sporu, rekonstruuje sposoby, jakimi prawoznawstwo usiłowało rozstrzygnąć kolizję pomiędzy specyfiką tych norm a ukształtowanym na tle tradycyjnego modelu normy prawnej zestawem pojęć. The Author presents the consequences of changes to the law, related to economic planning norms, in the legal language, on the basis of the dispute around these norms. By acknowledging the importance of the methodological consequences of the dispute, he reconstructs the ways in which legal science has attempted to resolve the conflict between the specific nature of these norms and the set of concepts formed against the background of the traditional model of the legal norm.